Collusion enforcement in repeated first‐price auctions. Issue 4 (25th November 2022) - Zhang, Wenzhang
Abstract : In the context of repeated first‐price auctions, we explore how a bid‐rigging cartel can simultaneously overcome the difficulty of soliciting truthful private information about valuations and the difficulty of enforcing its internal mechanism. Focusing on the class of trigger‐strategy collusive agreements, we explicitly characterize the optimal collusive agreement for any given discount factor. Making use of the characterization, we also explore how a long‐run seller can use a reserve price to fight the cartel.